Techno-functional of peanut flour substituting on hybrid chicken meatball physico-chemical and nutritional qualities - Soklin Son; Sreymom Hun; Md Anisur Rahman Mazumder; Lutz Grossmann; Passakorn Kingwascharapong; Samart Sai-ut; Pittaya Chaikham; Young Hoon Jung; Saroat Rawdkuen (Current Research in Food Science)
Consumer demand for healthy and sustainable food has driven the development of alternative meat products. This study investigated the effects of substituting peanut flour for chicken meat in meat balls. The hybrid chicken meat balls (HCM) were prepared by replacing chicken breast with 0, 25, 50, and 75 % peanut flour. Proximate composition, physico-chemical properties, textural quality, and protein patterns of HCM were determined. The protein (18.15–20.78 %), fat (0.13-18.71%), fiber (0.56–1.82 %), and ash (1.53–2.32 %) content increased with an increase in peanut flour. The highest cooking yield (99.16 %) was observed at 75 % peanut flour HCM, resulting in the highest juiciness (14.92 %). Texture profile analysis suggested that sample 25 % peanut flour HCM exhibited the most promising textural attributes and higher flour contents resulted in a decline in most textural attributes. HCM with 25 % peanut flour displayed a dense and continuous protein network, whereas 50 and 75 % peanut flour HCM had a looser, more porous structure. The amino acid profile of 25 % peanut flour HCM showed a significant presence of essential amino acids. The study concludes that substituting 25 % peanut flour improves protein and fiber content while maintaining desirable textural attributes, suggesting that peanut flour is a promising and sustainable option for meat ball production.